Marketing Mix and Psychology on Purchase Decision and Repurchase in the Creative Industry - Puspita, Dyah Rangga (International Journal Labs, 2022)
Background: Some factors that affect the success of the creative economy such as purchasing by consumers include the marketing mix’ influence, psychological influences, socio-cultural influences, and the influence of the situation/environment. Satisfaction with the first purchase is a factor that affects the repurchase intention. Aim: This research aimed at discovering the influence of mixed marketing and psychological condition on purchase decisions and repurchase for the creative industry. Method: This is explanatory research. The approach used is quantitative, with a sample number of 91 out of 162 populations. Primary data collection using questionnaires was conducted. The data analysis used in this study is descriptive analysis and path analysis. Findings: The first hypothesis H1 received is